Analisis Tren Korupsi Pengelolaan Keuangan Dana Pemerintah Desa - Risky Amalia R; Kasmayanti Kasmayanti; Ristha Dwi Puspita; Nita Hasnita (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the trends of corruption in financial management within village governments in Indonesia following the implementation of Law No. 6 of 2014 on Villages, which grants broader authority to villages in managing the Village Fund (DD) and Village Fund Allocation (ADD). Since the enactment of this policy, corruption cases involving village heads, village officials, and external actors have shown increasingly diverse and complex patterns. Employing a qualitative-descriptive approach through literature review, regulatory analysis, and examination of reports from oversight institutions, this research identifies the dominant forms of misuse and the underlying factors driving corruption. The findings indicate that the most prevalent corruption practices include embezzlement of funds, budget mark-ups, fictitious procurement of goods and services, manipulation of accountability reports, and unlawful deductions of social assistance. Contributing factors include weak internal and external oversight mechanisms, limited financial management capacity among village officials, entrenched patronage-based political culture, lack of transparency, and low community participation in monitoring village budgets. This study asserts that corruption at the village level significantly undermines development effectiveness, government accountability, and public trust. Therefore, it emphasizes the need for improved financial governance through digitalized management systems, capacity building for village officials, strengthened community-based supervision, and stricter law enforcement to mitigate corruption.